Predictors of Intensive Care Unit Nurses’ Practice of Evidence-Based Practice Guidelines - Abuejheisheh, Ashraf (Inquiry, 2020)
Although many studies discussed evidence-based practice among general nurses, few studies were found by the researchers among intensive care unit nurses. Also, no study has been conducted to investigate the predictors of evidence-based practice among intensive care unit nurses in Jordan. Therefore, this study aims to identify the predictors of evidence-based practice among intensive care unit nurses in Jordan. A descriptive cross-sectional design was used to conveniently recruit 132 participants. Self-reported questionnaires were utilized including the Evidence-Based Practice Questionnaire and Evidence-Based Practice barrier scale. Participants’ rate of evidence-based practice was 60% (M = 4.2/7), which was significantly correlated with their knowledge (r = 0.739, P < .01) and attitudes (r = 0.564, P < .01) of evidence-based practice. The results revealed a 2-predictor model that explained 62.2% of the variance in evidence-based practice among intensive care unit nurses. The 2 variables were attitude (β = 0.245) and knowledge (β = 0.563). The outcomes of this study added new information regarding the prediction of evidence-based practice among intensive care unit nurses. An educational program for nurses regarding this issue is crucial to improve their practice aiming at enhancing nursing care. Also, nursing schools should update their curricula to explain the importance of evidence-based practice and to enhance students’ competencies in research utilization and statistical skills.